2020
DOI: 10.1111/echo.14611
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Doppler echocardiography and right heart catheterization assessment of systolic pulmonary artery pressure in patients with severe aortic stenosis

Abstract: Objectives The aim of this study was to investigate reliability and accuracy of noninvasive measurement method by echocardiography compared to invasive measurement of systolic pulmonary artery pressure (SPAP) in a large cohort of aortic stenosis (AS) patients. Background Pulmonary hypertension (PH) is common in patients with cardiac disease, especially in left heart disease like severe AS. Invasive measurement by right heart catheterization (RHC) is the gold standard to assess pulmonary pressures. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Besides, research has also suggested that the non‐invasive evaluation of pulmonary arterial pressure by transthoracic echocardiography (TTE) correlates well with invasive measurements, and it is a reliable method for the assessment of pulmonary circulation 19,20 . Moreover, TTE is very suitable for the non‐invasive diagnosis of PAH and has an acceptable specificity and sensitivity in detecting PAH 21 . Therefore, we comprehensively evaluated the cardiac structure and function through TTE and blood pressure metre.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, research has also suggested that the non‐invasive evaluation of pulmonary arterial pressure by transthoracic echocardiography (TTE) correlates well with invasive measurements, and it is a reliable method for the assessment of pulmonary circulation 19,20 . Moreover, TTE is very suitable for the non‐invasive diagnosis of PAH and has an acceptable specificity and sensitivity in detecting PAH 21 . Therefore, we comprehensively evaluated the cardiac structure and function through TTE and blood pressure metre.…”
Section: Resultsmentioning
confidence: 99%
“…An sPAP ≥40 mmHg was used as the cut-off value to determine PH in accordance with the current literature [22][23][24]. In particular, Schewel et al [25] compared echocardiographically obtained sPAP with invasively RHC obtained sPAP data. The correlation coefficient of r = 0.820 was in a very satisfactory range.…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…The simplified Bernoulli equation (4 × TRV 2 ) + RAP was applied to obtain a sPAP result. Different sPAP (40, 45 and 50 mmHg) values were used to determine PH in accordance with the current literature [ 10 , 11 , 12 , 13 , 14 ]. An illustration about the echocardiographic measurement is provided in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%